Association of microabrasion and tooth whitening with LED/laser system in the treatment of incisor hypomineralization: 3-year follow-up - Costa, Joatan Lucas de Sousa Gomes [UNESP]; Nogueira, Básia Rabelo [UNESP]; de Oliveira Junior, Osmir Batista [UNESP]; Pretel, Hermes [UNESP] (Elsevier, 2021)
The hypomineralization of enamel is characterized as a defect in the quality of the enamel during the maturation process. This presents with clinical consequence as a whitish and rough appearance that effects the aesthetics of the dental elements. In recent years there has been a significant increase in this pathology, which has led to a great demand from professionals in the search for knowledge and appropriate technique to treat cases. Minimally invasive therapy may be sufficient for the aesthetic return of the altered enamel. Thus, the present clinical case aimed to present an aesthetic treatment of enamel hypomineralization in the upper incisors with a minimally invasive approach of association of microabrasion with low concentration tooth whitening photoaccelerated by violet LED and infrared laser. The follow-up of the case was performed for 3 years and the association of the techniques proved effective in returning the aesthetics and well-being of the patient, appearing as a good conservative alternative for the treatment of enamel hypomineralization.
Keywords: Hydroxide peroxide; LED; Microabrasion; Molar incisor hypomineralization; Tooth whitening